Between Revisionist and Status Quo: The Case of China’s Leadership in the AIIB - Yuliantoro, Nur Rachmat; Dinarto, Dedi (Jurnal Hubungan Internasional, 2019)
This article seeks to understand China’s foreign policy today by assessing its leadership in the Asian Infrastructure Investment Bank (AIIB), using the scholarly term of ‘contested multilateralism’ coined by Julia Morse and Robert Keohane. We argue that since the beginning of the 21st century, China has managed to improve its image as a new global power through the transformation of its foreign policy. In expanding its political sphere, China is using not only peripheral diplomacy but also cross-regional diplomacy strategies through the existing bilateral and multilateral mechanisms. Within this context, we look at a specific case of the creation of the AIIB as evidence of China’s greater participation in the global political economy realm. The AIIB can be seen as how China practices multilateralism in its foreign policy as it is trying to meet domestic, regional, as well as global development and economic challenges. This article argues that the creation of AIIB is not only the implication of China’s fiscal and trade policy, nor merely to solve the regional infrastructure gap in Asia, but also to challenge the U.S. (and Japan) influence through the Asian Development Bank (ADB), in which China possesses minor political power to accommodate its political economic interests.